Electrode modification using porous layers. Maximising the analytical response by choosing the most suitable voltammetry: Differential Pulse vs Square Wave vs Linear sweep voltammetry - Laborda, E; Molina, A; Martinez-Ortiz, F; Compton, R (2012)
The analytical benefits obtained from electrode modification with conductive porous layers, a common practice in the development of electrochemical (bio)sensors, are examined for the main electroanalytical techniques: differential pulse, square wave and linear sweep voltammetry. The electrochemical response is analyzed in terms of the effect of the modification on the electrode kinetics and on the diffusion transport of the target species. With respect to the former, the gain in the current predicted by simple enhancement of the electrode kinetics is analyzed, pointing out the improvement of the analytical sensitivity predicted in each voltammetric technique. Regarding the contribution of the thin-layer diffusion of the electroactive species trapped between the layers, we show that this gives rise to the lowering of the peak potential and the narrowing of the voltammograms, which can be wrongly attributed to electrocatalytic properties of the modified surface. In order to discriminate between electrocatalytic and mass transport effects, diagnosis tests are presented for differential pulse and square wave voltammetry. © 2011 Elsevier Ltd.